2010
DOI: 10.1186/1471-2458-10-194
|View full text |Cite
|
Sign up to set email alerts
|

Parent and child physical activity and sedentary time: Do active parents foster active children?

Abstract: BackgroundPhysical activity has many positive effects on children's health while TV viewing has been associated with adverse health outcomes. Many children do not meet physical activity recommendations and exceed TV viewing guidelines. Parents are likely to be an important influence on their children's behaviour. There is an absence of information about the associations between parents' and children's physical activity and TV viewing.MethodsYear 6 children and their parent were recruited from 40 primary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
192
4
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(223 citation statements)
references
References 49 publications
20
192
4
7
Order By: Relevance
“…13,14 This is likely due in part to varying study methods, and in particular the widespread use of self-report measures of physical activity. 22,23 Using an objective measure of physical activity (accelerometers 20 and pedometers 24 ), studies in older children report positive associations between children' s and parents' physical activity. In preschool-aged children, several small studies also reported positive associations between child' s and maternal, 17 paternal, 10,17 and parental physical activity levels 23 by using objectively measured activity.…”
mentioning
confidence: 99%
“…13,14 This is likely due in part to varying study methods, and in particular the widespread use of self-report measures of physical activity. 22,23 Using an objective measure of physical activity (accelerometers 20 and pedometers 24 ), studies in older children report positive associations between children' s and parents' physical activity. In preschool-aged children, several small studies also reported positive associations between child' s and maternal, 17 paternal, 10,17 and parental physical activity levels 23 by using objectively measured activity.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] Child TVV is also affected by coviewing, eating meals while watching television, and the establishment of household rules and regulations about media use, such as limits on the amount of television time. 14,15 Household access to television, in particular, having a television in the child' s bedroom, is associated with increased television time.…”
mentioning
confidence: 99%
“…The more parents watch television, engage in other leisure time screen-related sedentary activities, or simply spend time being inactive, the higher the risk is that their children will too (e.g., He, Harris, Piche, & Beynon, 2009;Jago, Fox, Page, Brockman, & Thompson, 2010).…”
Section: Physical Activitymentioning
confidence: 99%